The Report on Relations Between Anglican and Presbyterian Churches - Sykes, Norman (Scottish journal of theology, 1957)
‘Shall two walk together except they be agreed?‘ may well been a widespread question asked on both sides of the Border when the appointment of a joint Committee of Representatives, nominated respectively by the Archbishop of Canterbury and by the General Assembly of the Church of Scotland, to consider means of establishing closer relations between the Anglican and Presbyterian Churches was announced. The Report entitled ‘Relations between Anglican and Presbyterian Churches’ offers a provisional answer to this question, by affording evidence of a surprising degree of mutual rapprochement and by setting forth the bases for further action. Perhaps this measure of agreement is more surprising than ought to have been the case; for the history of the two national, established Churches of England and Scotland indicates how near they have been to each other in polity in the past; and how fortuitous were the circumstances which drove them apart. ‘This is the ideal which springs to light in the last months of 1558’ wrote F. W. Maitland of the relationship of the two nations at the accession of Elizabeth I, ‘deliverance from the toils of foreign potentates; amity between two sister nations; union in a pure religion.’ A Scottish contemporary, William Maitland indeed wrote to William Cecil in England, that ‘earnest embracing of religion will join us straitly together’. It was a consummation then devoutly to be wished; and no less still to be desired in the reign of Elizabeth II after the lapse of four centuries.